The Influence of Transformational Leadership on Employee Performance at the Mataram City Environmental Service - Nur Indry; Muhammad Ali; M. Ariy Dermawan S. (Lembaga Penerbitan dan Publikasi Ilmiah Yayasan Pendidikan Tumpuan Bangsa, 2026)
Employee performance is an important factor in determining the success of public organizations in delivering public services. One factor that is believed to influence employee performance is transformational leadership. This study aims to analyze the effect of transformational leadership. This study aims to analyze the effect of transformational leadership on employee performance at the Environmental Agency of Mataram City. This research employed a quantitative approach using an associative method. The population consisted of 528 employees, while 84 respondents were selected using the Slovin formula. Data were collected through questionnaires using a Likert scale and analyzed using simple linear regression with SPSS version 25. The results indicate that transformational leadership has a positive and significant effect on employee performance, with a regression coefficient of 0.842, a t-value of 13.419, and a significance level of 0.000. Furthermore, the coefficient of determination (R Square) was 0.687, indicating that transformational leadership explains 68.7% of the variation in employee performance. These findings demonstrate that better implementation of transformational leadership leads to higher employee performance at the Environmental Agency of Mataram City.